Dynamic Bandwidth Allocation for Internet of Things System Using Elastic Wireless Local Area Network - I Putu Sudharma Yoga; Gede Sukadarmika; Linawati Linawati (Universitas Syiah Kuala, 2021)
Rapid technological development, triggering various applications development that are increasingly innovative. One of them is the Internet of Things (IoT) system that makes human works easier and more effective. Along with sensor technology development in monitoring and controlling through IoT systems, a mechanism is needed to manage bandwidth so that IoT system can function optimally, especially in buildings designated as public areas. Smart building supported by various integrated sensors to maintain safety and comfort in the area. This study proposes the application of Elastic WLAN as a model for dynamic bandwidth management in IoT systems. In this model, IoT bandwidth changes automatically according to the number of traffic measurements for each IoT connected to the network As an effort to determine the performance of the elastic WLAN mechanism, this study succeeded in developing a prototype IoT device that implements Elastic WLAN on an Access-Point Raspberry Pi by using two temperature sensors placed in separate locations. The system successfully allocates bandwidth to each IoT according to the amount of data input from each temperature sensor installed. The higher the amount of data captured by the sensor, the system will automatically allocate the higher bandwidth to the sensor system, and vice versa.